Valuation by Approximation: A Comparison of Alternative Option Valuation Techniques - Geske, Robert; Shastri, Kuldeep (Journal of Financial and Quantitative Analysis, 1985)
Robert Geske, Kuldeep Shastri, Valuation by Approximation: A Comparison of Alternative Option Valuation Techniques, The Journal of Financial and Quantitative Analysis, Vol. 20, No. 1 (Mar., 1985), pp. 45-71